Dissipative particle dynamics simulations of end-cross-linked nanogels - Lenzi, Veniero (2021)
Nanogels, due to their unique properties, have potential for promising applications in several fields. There is a growing interest in understanding which are the mechanisms controlling their properties, as those depend not only on composition but also on internal structure. In this work, dissipative particle dynamics simulations were applied to simulate the formation of nanogels from monodisperse end-functionalised polymer chains, with the cross-linking reaction modelled using a distance-based algorithm, including a reversible intermediate step. Nanogel properties are studied by calculating their swelling transition curves and structure properties, such as network defects and entanglement state. Various chain lengths, reaction schemes, nanogel in silico synthesis methods and solvent ratios are compared and discussed, showing how these factors influence the nanogel swelling behaviour and structure. Our results show that, in order to be compared with experiments, nanogel simulations should carefully consider processing parameters.